2013
DOI: 10.3201/eid1911.130792
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fever with Thrombocytopenia Syndrome, South Korea, 2012

Abstract: We report a retrospectively identified fatal case of severe fever with thrombocytopenia syndrome (SFTS) in South Korea from 2012. SFTS virus was isolated from the stored blood of the patient. Phylogenetic analysis revealed this isolate was closely related to SFTS virus strains from China and Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
338
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(372 citation statements)
references
References 9 publications
6
338
0
8
Order By: Relevance
“…The virus emerged in rural areas of Hubei province, China, in 2009, and since that time the virus has been detected in many other areas throughout China; subsequently, isolation from patients, coupled with retrospective serological studies, has revealed the presence of the virus in Japan and South Korea as well (18)(19)(20). Here we describe the development of a reverse genetics system that allows the recovery of infectious viruses entirely from transfected cDNA clones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus emerged in rural areas of Hubei province, China, in 2009, and since that time the virus has been detected in many other areas throughout China; subsequently, isolation from patients, coupled with retrospective serological studies, has revealed the presence of the virus in Japan and South Korea as well (18)(19)(20). Here we describe the development of a reverse genetics system that allows the recovery of infectious viruses entirely from transfected cDNA clones.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of SFTSV RNA was highest in H. longicornis, a species that has a widespread geographical distribution outside China including Korea, Japan, Australia, New Zealand, and the Pacific Islands (17). The subsequent reports of SFTSV-positive ticks and confirmed cases of disease in South Korea (18,19) and Japan (20) indicate that SFTSV and SFTSV-like viruses may have a broad geographical distribution.…”
mentioning
confidence: 96%
“…Four deaths due to SFTSV infection were recently reported in Japan (3), and 14 cases of SFTSV (with 9 deaths) were confirmed in South Korea during 2012 to 2013 (4). Clinical signs of the disease mainly include severe fever, thrombocytopenia, and leukopenia syndrome, frequently with gastrointestinal symptoms such as diarrhea and abdominal pain.…”
mentioning
confidence: 99%
“…Originally described in the Henan and Hubei provinces in China (17), SFTSV has now been found to be more widespread in China (18) and has also been isolated in Japan and South Korea, suggesting a more widespread distribution (19,20). HRTV isolates have so far been restricted to Missouri and Tennessee in the United States, with 10 cases and 2 fatalities (21-23), but one serological survey suggested a widespread occurrence of antigenically similar viruses in farm animals throughout Minnesota (24).…”
mentioning
confidence: 99%